The Phonemic − Syllabic Comparisons of Standard Malay and Palembang Malay Using a Historical Linguistic Perspective - Novita Arsillah (Universitas Pendidikan Indonesia (UPI), 2013)
This study is a historical linguistic investigation entitled The Phonemic − Syllabic Comparisons of Standard Malay and Palembang Malay Using a Historical Linguistic Perspective which aims to explore the types of sound changes found in Palembang Malay. The investigation uses a historical linguistic comparative method to compare the phonemic and syllabic changes between an ancestral language Standard Malay and its decent language Palembang Malay. Standard Malay refers to the Wilkinson dictionary in 1904. The participants of this study are seven native speakers of Palembang Malay whose ages range from 20 to 40 years old. The data were collected from the voices of the participants that were recorded along group conversations and interviews. This study applies the theoretical framework of sound changes which proposed by Terry Crowley in 1997 and Lily Campbell in 1999. The findings show that there are nine types of sound changes that were found as the results, namely assimilation (42.35%), lenition (20%), sound addition (3.53%), metathesis (1.18%), dissimilation (1.76%), abnormal sound changes (3.53%), split (13.53%), vowel rising (10.59%), and monophthongisation (3.53%). Keywords: Historical linguistics, standard Malay, Palembang Malay, comparative method, sound change, phoneme, syllable.